Retrospective Study on the Application of Enhanced Recovery After Surgery Measures to Promote Postoperative Rehabilitation in 50 Patients With Brain Tumor Undergoing Craniotomy - Feng, SongShan; Xie, Bo; Li, ZhenYan; Zhou, XiaoXi; Cheng, Quan; Liu, ZhiXiong; Tao, ZiRong; Zhang, MingYu (Frontiers in Oncology, 2021)
Objective: To investigate whether enhanced recovery after surgery (ERAS) can promote postoperative rehabilitation in neurosurgical craniotomy. Methods: The clinical data of 100 patients with brain tumor undergoing craniotomy in the Department of Neurosurgery, Xiangya Hospital, Central South University from January 2018 to August 2020 were collected, including 50 patients in the ERAS group and 50 patients in the control group. T test, Wilcoxon rank sum test and chi square analysis were used to compare the clinical characteristics, prognosis and hospitalization time between the two groups. Results: There was no significant difference in gender, age and other general clinical data between the two groups (P > 0.05). The days of antiemetic drugs applied in ERAS group were less than those in control group (1.00d vs 2.00d, P = 0.003), and the proportion of patients requiring analgesic drugs was lower than that of control group (30% vs 52%, OR = 0.41, 95% CI 0.18-0.93, P = 0.031). The time of urinary catheter removal and patient ambulation in ERAS group were shorter than those in control group (16.00 h vs 24.00 h, 1.00 d vs 2.00 d, P < 0.001 respectively), and the length of hospital stay (LOS) in ERAS group was shorter than that in control group (Total LOS: 13.00 d vs 15.50 d, Postoperative LOS: 7.00 d vs 10.00 d, P < 0.001 respectively). By analyzing the prognosis of patients in ERAS group and control group, we found that there was no significant difference in postoperative complications and KPS score of 1 month after operation between the two groups. Conclusion: The application of ERAS in craniotomy can accelerate the postoperative recovery of patients, and does not increase the perioperative risk, which is worthy of wide application. However, whether ERAS measures can reduce the postoperative complications and improve the prognosis of patients still needs more large-scale case validation and multi-center collaborative study.